Karakteristik sosis berbahan dasar jamur tiram putih (Pleurotus ostreatus) dan tahu serta penambahan tepung kacang merah (Phaseolus vulgaris L.) dan susu skim - Merkuria Karyantina; Ginza Desy Pramesti; Yustina Wuri Wulandari (AGROINTEK, 2025)
White oyster mushrooms and tofu can used as an alternative raw materials in making sausage. Red bean flour can substitute for skim milk because it is high nutritional. The aimed of the research was to determine the best formulation of sausage with white oyster mushroom and tofu, also the addition of red bean flour and skim milk, which based on highest protein content, also level of preference. The experimental design was a completely randomized design (CRD) with the first factor was variation oyster mushrooms and tofu (75% : 25%, 50% : 50%, 25% : 75%) and the second factor was variation of red bean flour and skim milk (1:3, 2:2, 3:1). The result indicated that the best formulation of sausage made from oyster mushroom and tofu with the addition of the red bean flour and skim milk based on the best protein content and highest preference of panelist were treatment of 75% of oyster mushrooms : 25% of tofu, and the addition of red bean flour:skim milk 3:1 with  moisture content 60.53%,  ash content 2.99%, protein content 15.88%, fat content 6.45%, and carbohydrate content 14.14%. Organoleptic analysis was color 4.09 (dark), flavor of mushroom 3.41 (quite felt), flavor of tofu 2.25 (less felt), savory taste 3.94 (tasty), chewy 3.29 (quite) and overall, 3.33 (preferred)